Two-component load-bearing adhesive and preparation method thereof
Through the design of double -component load -type adhesives, the cross -linking response of epoxy resin and other raw materials solves the problem of the existing LPG ship glue. High -performance adhesive.
Patent Information
- Application Number
- CN202411930012.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-25
AI Technical Summary
It is difficult for existing LPG marine glue to have excellent bonding strength, compression strength, toughness and heat resistance at the same time.
Using dual -component load -bearing adhesives, epoxy resin, glass fiber, aluminum and aluminum hydroxide and other raw materials are mixed according to a specific proportion to form a component A and B components, and disorderly form through intricate cross -linking reactions to form disorderly reactions Linking network structure.
The adhesive has achieved excellent bonding strength, compressive strength, toughness and heat resistance, meeting the high requirements of LPG marine adhesives.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of adhesives, and specifically relates to a two-component load-bearing adhesive and a preparation method thereof. Background Art
[0002] Liquefied petroleum gas (LPG) ships are special transport ships and corresponding shore-based tank systems that are mainly used to store liquefied gas at a liquid temperature of minus 163 degrees Celsius. The containment system of the liquid cargo tank of the LPG ship, that is, the isolation barrier and thermal insulation system of the liquid cargo tank, is the core technology of the LPG ship. Its main functions are: it has a completely dense metal film to ensure that there is no leakage of LPG; it has good thermal insulation and insulation capabilities to prevent the hull from being cooled and losing strength and toughness, and is used to maintain the temperature of the cargo in the cabin and the safety of the hull during transportation.
[0003] LPG marine adhesive is an adhesive used for specific parts and structures of ships. It needs to be able to firmly bond various components in the hull structure, such as tanks, pipes, valves, etc., to ensure that these components will not loosen or fall off due to vibration, impact and other factors during transportation. It needs to have good heat resistance, high bonding strength, high compression strength and toughness to improve the carrying capacity of the ship. However, it is difficult for existing LPG marine adhesives to have excellent bonding performance, compression strength, toughness and heat resistance at the same time. Summary of the invention
[0004] The present application provides a two-component load-bearing adhesive and a preparation method thereof, aiming to provide an adhesive having excellent bonding strength, compression strength, toughness and heat resistance.
[0005] The first aspect of the present application provides a two-component load-bearing adhesive, the two-component load-bearing adhesive comprising a component A and a component B in a mass ratio of 1: (0.2-0.5); Component A includes the following raw materials in parts by weight: 50 parts of epoxy resin; and based on 50 parts of epoxy resin: 20-40 parts of glass fiber; 2-10 parts of alumina; 10-20 parts of aluminum hydroxide; 1-13 parts of plasticizer; 0.05-1 part of modifier; wherein the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin; Component B includes the following raw materials in parts by weight: 100 parts of a curing agent and 0-5 parts of an auxiliary agent based on 100 parts of the curing agent; the curing agent includes polyethylene polyamine, polyether amine, phenolic amine and polyamide.
[0006] In a feasible implementation manner of the first aspect of the present application, the mass ratio of polyethylene polyamine, polyether amine, phenolic amine and polyamide is 2: (0.6-4): (0.06-2): (1.3-10).
[0007] In a feasible implementation manner of the first aspect of the present application, the mass ratio of polyethylene polyamine, polyether amine, phenolic amine and polyamide is 2: (1-2): (0.5-1): (2-5), and optionally 2: 1: 1: 3.
[0008] In a feasible implementation manner of the first aspect of the present application, the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin is (5-10):(1-3):1, and can be optionally 7:2:1.
[0009] In a feasible implementation manner of the first aspect of the present application, the number of carbon atoms in the repeating structural unit of the polyamide is 4 to 10, and optionally 4 to 8.
[0010] In a feasible implementation manner of the first aspect of the present application, component B also includes the following raw materials in parts by weight: 20-40 parts of glass fiber; 10-30 parts of filler (such as 2-10 parts of aluminum oxide; 10-20 parts of aluminum hydroxide).
[0011] In a feasible implementation of the first aspect of the present application, the modifier includes one or more of a silane coupling agent, a leveling agent and a defoaming agent; and / or the auxiliary agent includes one or more of a catalyst, a dispersant and a defoaming agent.
[0012] The second aspect of the present application provides a method for preparing a two-component load-bearing adhesive, comprising: Mix bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to obtain a first mixture; mix glass fiber, aluminum hydroxide, aluminum oxide, a modifier and a plasticizer to obtain a second mixture; mix the first mixture and the second mixture evenly to obtain component A; Mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide uniformly to obtain component B; Mix component A and component B in a mass ratio of 1:(0.2~0.5) to obtain a two-component load-bearing adhesive.
[0013] In a feasible implementation of the second aspect of the present application, bisphenol A epoxy resin, bisphenol F epoxy resin, and alicyclic epoxy resin are mixed to obtain a first mixture; glass fiber, aluminum hydroxide, aluminum oxide, a modifier, and a plasticizer are mixed and stirred to obtain a second mixture; and the first mixture and the second mixture are uniformly mixed to obtain the step of component A, comprising: Place bisphenol A epoxy resin in a container, add bisphenol F epoxy resin and alicyclic epoxy resin in a predetermined mass ratio, mix, and stir at high speed for 5 to 20 minutes to obtain a first mixture; place glass fiber, aluminum hydroxide, aluminum oxide, modifier and plasticizer in a high-speed disperser with predetermined weight portions, mix and stir for 5 to 20 minutes, and dry at 80°C to 120°C for 1h to 2h to obtain a second mixture; mix the first mixture and the second mixture in a mass ratio of 1:1 until no obvious stratification occurs to obtain component A.
[0014] In a feasible implementation manner of the second aspect of the present application, the step of uniformly mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide to obtain component B includes: placing polyethylene polyamine, polyether amine, phenolic amine and polyamide in a high-speed stirrer, mixing and stirring for 15 to 35 minutes to obtain component B.
[0015] The bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin such as 2021p epoxy resin in component A of the adhesive of the present application undergo an intricate cross-linking reaction with four different types of curing agents, polyethylene polyamine, polyether amine, phenolic amine and polyamide, in component B, to promote the formation of a disordered cross-linked network structure, forming a soft and hard embedded polymer, and wrapping the glass fiber, aluminum hydroxide and aluminum oxide powders in the cross-linked network of the epoxy resin, so that the linear resin is transformed into a tough bulk solid, thereby obtaining an adhesive having excellent bonding strength, compressive strength, toughness and heat resistance.
[0016] Bisphenol A epoxy resin is a thermoplastic resin, and its cured product has high strength and bonding strength, corrosion resistance and electrical properties, but its heat resistance and toughness are not high, and its moisture and heat resistance and weather resistance are insufficient. Bisphenol F epoxy resin has a low viscosity, which is about 1 / 3 of the viscosity of bisphenol A epoxy resin. It has good impregnation properties for fibers, but also has slightly lower heat resistance. The adhesive of this application is mainly used for LPG marine adhesives, which require strong load-bearing capacity, strong toughness and good heat resistance. After a large number of experimental studies and demonstrations, the inventors have shown that epoxy resins require bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to be matched with each other to achieve the above-mentioned effect. Among them, alicyclic epoxy resin contains an alicyclic structure, and the epoxy group is located on the alicyclic structure, which can form a tight rigid molecular structure. Compared with bisphenol A epoxy resin, its curing properties and the physical properties of the cured product show very different characteristics. The addition of alicyclic epoxy resin increases the cross-linking density and disorder of the reaction, increases the compressibility of the adhesive, and overall makes the adhesive have the characteristics of excellent mechanical strength, low shrinkage, strong toughness and low thermal expansion coefficient.
[0017] The types of curing agents include aliphatic amines, ester ring amines, aromatic amines, polyamides, anhydrides, and aromatic curing agents. The choice of curing agent will also affect the performance of the adhesive formed by cross-linking with the epoxy resin. The curing agent matched with the epoxy resin in the present application includes curing agents of different segment lengths, which can further promote the formation of a disordered system. For example, the low molecular weight polyamide has a more complex composition, contains primary amines, secondary amines and amide groups, can cure epoxy resins at room temperature, has good adhesion to metals, glass, ceramics, wood, etc., can play an internal toughening role, and after reacting with the epoxy resin of the present application, the toughness of the resulting adhesive is further enhanced. DETAILED DESCRIPTION
[0018] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0019] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0020] In the description herein, when a composition is described as containing, comprising or including specific components, or when a process is described as containing, comprising or including specific process steps, it is expected that the composition of the present application also consists essentially of or consists of the components, and the process of the present application also consists essentially of or consists of the process steps.
[0021] The use of the terms "including," "comprising," "containing," and "having" should generally be interpreted as open ended and non-limiting unless expressly stated otherwise.
[0022] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means more than two.
[0023] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0024] Epoxy resin is a typical cross-linked thermosetting polymer material. It has many excellent properties, such as good mechanical properties, excellent stability, strong adhesion and low shrinkage. It is widely used in related fields such as coatings, adhesives and civil engineering materials, and plays an important role in thermosetting resins.
[0025] The composition of epoxy adhesives is mainly epoxy resin matrix, curing agent, inorganic powder filler, and modifier. During the reaction process of common epoxy resin and curing agent, the chemical chains crosslink and entangle with each other to form a solidified product with a three-dimensional cross-linked structure. However, the colloid finally obtained has high hardness, low toughness, high brittleness and easy cracking, and poor impact resistance. LPG marine adhesive is an adhesive used for specific parts and structures of ships. The bearing point fixation of LNG / LPG storage tanks requires not only good thermal insulation and insulation capabilities, but also the ability to firmly bond various components in the hull structure, requiring high bonding strength, compression strength and toughness.
[0026] In view of this, the inventors provide a two-component load-bearing adhesive and a preparation method thereof in the present application, aiming to provide an adhesive having excellent bonding strength, compressive strength, toughness and heat resistance.
[0027] The first aspect of the present application provides a two-component load-bearing adhesive, the two-component load-bearing adhesive comprising a component A and a component B in a mass ratio of 1: (0.2-0.5); Component A includes the following raw materials in parts by weight: 50 parts of epoxy resin; and based on 50 parts of epoxy resin: 20-40 parts of glass fiber; 2-10 parts of alumina; 10-20 parts of aluminum hydroxide; 1-13 parts of plasticizer; 0.05-1 part of modifier; wherein the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin; Component B includes the following raw materials in parts by weight: 100 parts of a curing agent and 0-5 parts of an auxiliary agent based on 100 parts of the curing agent; the curing agent includes polyethylene polyamine, polyether amine, phenolic amine and polyamide.
[0028] The bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin in component A of the adhesive of the present application undergo an intricate cross-linking reaction with four different types of curing agents, polyethylene polyamine, polyether amine, phenolic amine and polyamide, in component B, to promote the formation of a disordered cross-linked network structure, forming a soft and hard embedded polymer, and wrapping glass fiber, aluminum hydroxide and aluminum oxide powders in the cross-linked network of the epoxy resin, so that the linear resin is transformed into a tough bulk solid, thereby obtaining an adhesive having excellent bonding strength, compressive strength, toughness and heat resistance.
[0029] Bisphenol A epoxy resin is a thermoplastic resin, and its cured product has high strength and bonding strength, corrosion resistance and electrical properties, but its heat resistance and toughness are not high, and its moisture and heat resistance and weather resistance are insufficient. Bisphenol F epoxy resin has a low viscosity, which is about 1 / 3 of the viscosity of bisphenol A epoxy resin. It has good impregnation properties for fibers, but also has slightly lower heat resistance. The adhesive of this application is mainly used for LPG marine adhesives, which require strong load-bearing capacity, strong toughness and good heat resistance. After a large number of experimental studies and demonstrations, the inventors have shown that epoxy resins require bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to be matched with each other to achieve the above-mentioned effect. Among them, alicyclic epoxy resin contains an alicyclic structure, and the epoxy group is located on the alicyclic structure, which can form a tight rigid molecular structure. Compared with bisphenol A epoxy resin, its curing properties and the physical properties of the cured product show very different characteristics. The addition of alicyclic epoxy resin increases the cross-linking density and disorder of the reaction, increases the compressibility of the adhesive, and overall makes the adhesive have the characteristics of excellent mechanical strength, low curing shrinkage, strong toughness and low thermal expansion coefficient.
[0030] The types of curing agents include aliphatic amines, ester ring amines, aromatic amines, polyamides, anhydrides, and aromatic curing agents. The choice of curing agent will also affect the performance of the adhesive formed by cross-linking with the epoxy resin. The curing agent matched with the epoxy resin in the present application includes curing agents of different segment lengths, which can further promote the formation of a disordered system. For example, the low molecular weight polyamide has a more complex composition, contains primary amines, secondary amines and amide groups, can cure epoxy resins at room temperature, has good adhesion to metals, glass, ceramics, wood, etc., can play an internal toughening role, and after reacting with the epoxy resin of the present application, the toughness of the resulting adhesive is further enhanced.
[0031] In some embodiments, the mass ratio of polyethylene polyamine, polyether amine, phenalkamine and polyamide is 2: (0.6-4): (0.06-2): (1.3-10).
[0032] In some embodiments, the polyethylene polyamine includes one or more of triethylenetetramine, diethylenetriamine, and tetraethylenepentamine.
[0033] In some embodiments, the mass ratio of polyethylene polyamine, polyether amine, phenolic amine and polyamide is 2: (1-2): (0.5-1): (2-5), optionally 2: 1: 1: 3.
[0034] The inventors have found that an adhesive with strong weighing capacity, strong bonding performance and better toughness can be obtained by adjusting the range of the above mass ratio in the curing agent. Too much polyethylene polyamine will lead to too fast curing rate, brittle system and poor toughness, too little will make the system soft and insufficient bearing capacity; polyether amine such as D400 plays a toughening role, too much will make the system soft, too little will make the system brittle and poor toughness; phenolic amine plays a role in promoting curing, too much will lead to strong reaction activity of the system, too fast reaction rate and short construction operation time; polyamide as the main curing agent has the effect of enhancing bonding force and increasing the toughness of the adhesive, and it has a good reaction effect when mixed with the other three in proportion.
[0035] In some embodiments, the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin is (5-10):(1-3):1, and can be 7:2:1.
[0036] Bisphenol A epoxy resin is a thermoplastic resin, but it is thermosetting. It can form a variety of cured products with excellent performance with a variety of curing agents, catalysts and additives, which can almost meet various usage requirements. It basically does not produce small molecule volatiles during curing, can be molded at low pressure, and can be dissolved in a variety of solvents. Bisphenol F epoxy resin is a new type of epoxy resin developed to reduce the viscosity of bisphenol A epoxy resin itself and have the same performance. Alicyclic epoxy resin contains an alicyclic structure, and the epoxy group is located on the alicyclic structure, which can form a tight rigid molecular structure. The alicyclic skeleton directly acts on the inside of the epoxy resin as a group structure. After curing, the crosslinking density increases, and the finished product has excellent mechanical strength, low shrinkage, and low thermal expansion coefficient.
[0037] The inventors have found that the mass ratio of the bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin can also affect the performance of the adhesive. The adhesive formed by the epoxy resin within the above mass ratio range has strong load-bearing capacity, low curing shrinkage and low thermal expansion coefficient.
[0038] In some embodiments, the carbon atoms of the repeating structural unit of the polyamide are 4 to 10, and optionally 4 to 8.
[0039] In the present application, low molecular weight polyamide, such as polyamide 651, can be selected. The low molecular weight polyamide curing agent has a relatively long fatty carbon chain in its molecule, which can play an internal toughening role and make the cured epoxy resin more tough. Therefore, the low molecular weight polyamide can be both a curing agent and a toughening agent.
[0040] In some embodiments, component B further comprises the following raw materials in parts by weight: 20-40 parts of glass fiber; 10-30 parts of filler (such as 2-10 parts of aluminum oxide; 10-20 parts of aluminum hydroxide).
[0041] In some embodiments, the modifier includes one or more of a silane coupling agent, a leveling agent, and a defoaming agent; and / or the auxiliary agent includes one or more of a catalyst, a dispersant, and a defoaming agent.
[0042] In the second aspect of the present application, a method for preparing a two-component load-bearing adhesive is provided, comprising: Mix bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to obtain a first mixture; mix glass fiber, aluminum hydroxide, aluminum oxide, a modifier and a plasticizer to obtain a second mixture; mix the first mixture and the second mixture evenly to obtain component A; Mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide uniformly to obtain component B; Mix component A and component B in a mass ratio of 1:(0.2~0.5) to obtain a two-component load-bearing adhesive.
[0043] In some embodiments, bisphenol A epoxy resin, bisphenol F epoxy resin, and alicyclic epoxy resin are mixed to obtain a first mixture; glass fiber, aluminum hydroxide, aluminum oxide, a modifier, and a plasticizer are mixed and stirred to obtain a second mixture; and the first mixture and the second mixture are mixed uniformly to obtain component A, comprising: Place bisphenol A epoxy resin in a container, add bisphenol F epoxy resin and alicyclic epoxy resin in a predetermined mass ratio, mix, and stir at high speed for 5 to 20 minutes to obtain a first mixture; place glass fiber, aluminum hydroxide, aluminum oxide, modifier and plasticizer in a high-speed disperser with predetermined weight portions, mix and stir for 5 to 20 minutes, and dry at 80°C to 120°C for 1h to 2h to obtain a second mixture; mix the first mixture and the second mixture in a mass ratio of 1:1 until no obvious stratification occurs to obtain component A.
[0044] In some embodiments, the step of uniformly mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide to obtain component B includes: placing polyethylene polyamine, polyether amine, phenolic amine and polyamide in a high-speed stirrer, mixing and stirring for 15 to 35 minutes to obtain component B.
[0045] The adhesive of the present application is easy to prepare and operate, and has simple curing conditions. It takes about 8 hours to fully cure at 80°C. Example
[0046] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0047] Example 1
[0048] A method for preparing an adhesive, the preparation process is divided into two parts: Preparation of component A: Take 35 parts of bisphenol A epoxy resin (Phoenix E51) and put it into a dry flask. Add 10 parts of bisphenol F epoxy resin (Nan Ya 170) and 5 parts of alicyclic epoxy resin 2021p epoxy resin according to the ratio of 7:2:1. Stir for 10 minutes under high-speed stirring of the stirrer. Use an electronic balance to weigh 30 parts of glass fiber, 15 parts of aluminum hydroxide, 5 parts of alumina, 5 parts of plasticizer, and 5% of the total mass of the three types of epoxy resins. Place the modifier in a high-speed disperser and mix the two for 10 minutes. Put the mixed powder into an oven and spread it flat at 100°C to dry for 1 hour. Then mix the solid and liquid phases evenly at a solid-liquid ratio of 50:50 until there is no obvious stratification to obtain component A. Preparation of component B: 20 parts of triethylenetetramine, 10 parts of polyetheramine D400 curing agent, 10 parts of phenolic amine (Liansheng LSC203) and 30 parts of polyamide 651 are placed in a dry flask in a mass ratio of 2:1:1:3. Stir and mix them for 25 minutes under a high-speed stirrer until the color is uniform and there is no obvious stratification, so as to obtain component B; When using, mix component A and component B in a mass ratio of 100:30 until the color is uniform, and then apply it on the object for bonding.
[0049] Example 2 Compared with Example 1, Example 2 mainly differs in that the mass ratio of triethylenetetramine, D400 curing agent, phenolic amine and polyamide is 2:5:2:1, and the total weight of the curing agent remains unchanged.
[0050] Example 3 Compared with Example 1, Example 3 mainly differs in that the mass ratio of triethylenetetramine, D400 curing agent, phenolic amine and polyamide is 2:1:1:5, and the total weight of the curing agent remains unchanged.
[0051] Example 4 Compared with Example 1, Example 4 mainly differs in that the mass ratio of triethylenetetramine, D400 curing agent, phenolic amine and polyamide is 2:2:0.5:5, and the total weight of the curing agent remains unchanged.
[0052] Example 5 Compared with Example 1, Example 5 mainly differs in that the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and 2021p epoxy resin is 13:1:1, and the total weight of the epoxy resin remains unchanged.
[0053] Example 6 Compared with Example 1, Example 6 mainly differs in that the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and 2021p epoxy resin is 10:4:1, and the total weight of the epoxy resin remains unchanged.
[0054] Example 7 Compared with Example 1, Example 7 mainly differs in that the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and 2021p epoxy resin is 5:3:1, and the total weight of the epoxy resin remains unchanged.
[0055] Example 8 Compared with Example 1, Example 8 mainly differs in that the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin and 2021p epoxy resin is 3:4:1, and the total weight of the epoxy resin remains unchanged.
[0056] Example 9 The main difference between Example 9 and Example 1 is that polyamide 1010 is used to replace polyamide 651.
[0057] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that 2021p epoxy resin is not added to component A, and bisphenol A epoxy resin is used instead in equal parts by weight.
[0058] Comparative Example 2 The main difference between Comparative Example 2 and Example 1 is that bisphenol F epoxy resin is not added to component A, and bisphenol A epoxy resin of equal weight is used instead.
[0059] Comparative Example 3 Compared with Example 1, the main difference between Comparative Example 3 is that the 2021p epoxy resin in component A is replaced by an equal weight portion of phenolic epoxy resin.
[0060] Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that polyamide 651 is not added to component B, but is replaced by an equal weight portion of triethylenetetramine.
[0061] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that no phenalkamine is added to component B, and an equal weight portion of triethylenetetramine is used instead.
[0062] Test Section The performance tests were carried out on the adhesives of various embodiments and comparative examples, and the test results are shown in Table 1 below.
[0063] Test method: Maximum Compression Load, Compression Modulus: Tested in accordance with ASTM D695-23.
[0064] Elongation, bonding strength: tested in accordance with GB / T 2567 standard.
[0065] Curing shrinkage: Tested in accordance with ISO 2577-2007 standard.
[0066] Punch shear strength: tested in accordance with ASTM D732-17 (2017) standard.
[0067] Hardness: Tested in accordance with GBT 43432.3-2023 standard.
[0068] Thermal Expansion Coefficient: Tested in accordance with ASTM D696-08 standard.
[0069] Table 1:
[0070] From the test results, it can be seen that the adhesive of the embodiment has excellent bonding strength, compression strength, toughness and heat resistance, especially high compression strength, strong toughness and excellent bonding strength. Its compression characteristics fill the gap of domestic load-bearing adhesives and can solve the problem that many downstream products want both excellent bonding strength and toughening and load-bearing. The adhesives of comparative examples 1 to 5 are not as good as those of the embodiment because they do not use the epoxy resin and curing agent mixed in the present application.
[0071] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A two-component load-bearing adhesive, characterized in that: The two-component load-bearing adhesive comprises component A and component B in a mass ratio of 1:(0.2-0.5); The A component includes the following raw materials in parts by weight: 50 parts of epoxy resin; and based on 50 parts of epoxy resin: 20-40 parts of glass fiber; 2-10 parts of aluminum oxide; 10-20 parts of aluminum hydroxide; 1-13 parts of plasticizer; 0.05-1 part of modifier; wherein the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin; The B component comprises the following raw materials in parts by weight: 100 parts of a curing agent and 0-5 parts of an auxiliary agent based on 100 parts of the curing agent; wherein the curing agent comprises polyethylene polyamine, polyether amine, phenolic amine and polyamide.
2. The two-component load-bearing adhesive according to claim 1, characterized in that: The mass ratio of the polyethylene polyamine, polyether amine, phenolic amine and polyamide is 2: (0.6-4): (0.06-2): (1.3-10).
3. The two-component load-bearing adhesive according to claim 1, characterized in that: The mass ratio of the polyethylene polyamine, polyether amine, phenolic amine and polyamide is 2: (1-2): (0.5-1): (2-5).
4. The two-component load-bearing adhesive according to claim 1, characterized in that: The mass ratio of the bisphenol A epoxy resin, the bisphenol F epoxy resin and the alicyclic epoxy resin is (5-10): (1-3):
1.
5. The two-component load-bearing adhesive according to claim 1, characterized in that: The carbon atoms of the repeating structural unit of the polyamide are 4 to 10.
6. The two-component load-bearing adhesive according to claim 1, characterized in that: The B component also includes the following raw materials in parts by weight: 20 to 40 parts of glass fiber; and 10 to 30 parts of filler.
7. The two-component load-bearing adhesive according to claim 1, characterized in that: The modifier includes one or more of a silane coupling agent, a leveling agent and a defoaming agent; And / or; the auxiliary agent includes one or more of a catalyst, a dispersant and a defoaming agent.
8. A method for preparing a two-component load-bearing adhesive, characterized in that: The preparation method comprises: Mix bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to obtain a first mixture; mix glass fiber, aluminum hydroxide, aluminum oxide, a modifier and a plasticizer to obtain a second mixture; mix the first mixture and the second mixture evenly to obtain component A; Mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide uniformly to obtain component B; The component A and the component B are mixed in a mass ratio of 1:(0.2-0.5) to obtain the two-component load-bearing adhesive.
9. The method for preparing the two-component load-bearing adhesive according to claim 8, characterized in that: The steps of mixing bisphenol A epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin to obtain a first mixture; mixing glass fiber, aluminum hydroxide, aluminum oxide, a modifier and a plasticizer to obtain a second mixture; and uniformly mixing the first mixture and the second mixture to obtain component A include: Place bisphenol A epoxy resin in a container, add bisphenol F epoxy resin and alicyclic epoxy resin in a predetermined mass ratio, mix, and stir at high speed for 5 minutes to 20 minutes to obtain a first mixture; place glass fiber, aluminum hydroxide, aluminum oxide, modifier and plasticizer in a high-speed disperser with predetermined weight parts, mix and stir for 5 minutes to 20 minutes, and dry at 80°C to 120°C for 1 hour to 2 hours to obtain a second mixture; mix the first mixture and the second mixture evenly until no obvious stratification occurs to obtain the A component.
10. The method for preparing the two-component load-bearing adhesive according to claim 8, characterized in that: The step of uniformly mixing polyethylene polyamine, polyether amine, phenolic amine and polyamide to obtain component B comprises: placing polyethylene polyamine, polyether amine, phenolic amine and polyamide in a high-speed stirrer, mixing and stirring for 15 minutes to 35 minutes to obtain component B.
Citation Information
Patent Citations
Anti-impact epoxy structural rubber and preparation method thereof
CN101724368A
High-strength high-toughness epoxy resin adhesive and preparation method thereof
CN102925091A
Two-component epoxy structural adhesive and method for preparing same
CN109439246A
Steel bonding structural adhesive and preparation method thereof
CN117683498A
Adhesive composition and laminate
CN118414395A
Cited By
Hot-pressing magnetic powder connecting adhesive and preparation method thereof
CN120209754A
Polyamide adhesive and insulating composite layer, and preparation methods therefor and use thereof
WO2026108180A1